2017
DOI: 10.1080/17435390.2017.1317863
|View full text |Cite
|
Sign up to set email alerts
|

Assessing nanomaterial exposures in aquatic ecotoxicological testing: Framework and case studies based on dispersion and dissolution

Abstract: The unique behavior of engineered nanomaterials (ENM) in aqueous media and dynamic changes in particle settling, agglomeration and dissolution rates is a challenge to the consistency, reliability and interpretation of standard aquatic hazard bioassay results. While the toxicological endpoints (e.g., survival, growth, reproduction, etc.) in ecotoxicity bioassays are largely applicable to ENMs, the standard methods as written for dissolved substances are confounded by the dynamic settling, agglomeration and diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The Organisation for Economic Co-operation and Development guidance describes how variation in substance concentration greater than AE20% should be addressed using modified experimental procedures or monitoring strategies (Petersen et al 2015). However, in cases where the period of dispersion stability and exposure in the water column is short (<12 h relative to bioassay durations) acute toxicity tests (48-h duration) may be considered relevant and conducted (Kennedy et al 2017).…”
Section: Monitoring the Dispersion Stability Of Graphene Oxide After ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Organisation for Economic Co-operation and Development guidance describes how variation in substance concentration greater than AE20% should be addressed using modified experimental procedures or monitoring strategies (Petersen et al 2015). However, in cases where the period of dispersion stability and exposure in the water column is short (<12 h relative to bioassay durations) acute toxicity tests (48-h duration) may be considered relevant and conducted (Kennedy et al 2017).…”
Section: Monitoring the Dispersion Stability Of Graphene Oxide After ...mentioning
confidence: 99%
“…In general, humic acid-containing dispersions have remained within (or close to) the limit of the 20% reduction of the nominal concentration. The use of modifications to reduce the strength of ionic testing media and pH alterations must consider the environmental relevance and test organism health and is not always possible (Martinez et al 2014;Kennedy et al 2017).…”
Section: Monitoring the Dispersion Stability Of Graphene Oxide After ...mentioning
confidence: 99%
“…Additional advantages of incorporating the photocatalyst into a 3D printable polymer includes the ability to augment the density to maintain catalysts in the photoactive zone as buoyant structures to overcome limitations of free powders or "slurries" which would otherwise agglomerate and settle. 28 This would allow the TiO 2 to be easily recoverable from complex environmental media which would prevent legacy contamination and subsequent physical 28 or photocatalytic effects 29 of the material on ecological receptors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, pioneering studies have demonstrated the fabrication of a variety of 3D printed TiO 2 composites (e.g., polylactic–hydroxyapatite–TiO 2 ; ceramic–polymer–nano-TiO 2 ; polyetheretherketone (PEEK)–TiO 2 ; polycarbonate (PC)–TiO 2 ). Recent demonstrated uses of AM structures for wastewater treatment included 3D printed polymer–zeolite composite geometries that successfully reduced ammonia concentrations in water and 3D printed polymer–photocatalyst composites having demonstrated proof-of-efficacy for degrading model organic contaminants. , Therefore, there is a strong technical basis for using AM to develop and test potential photocatalytic reactors to provide proof-of-principle performance and optimization that can aid in developing treatment structures that meet the site-specific demands. Additional advantages of incorporating the photocatalyst into a 3D printable polymer includes the ability to augment the density to maintain catalysts in the photoactive zone as buoyant structures to overcome limitations of free powders or “slurries” which would otherwise agglomerate and settle . This would allow the TiO 2 to be easily recoverable from complex environmental media which would prevent legacy contamination and subsequent physical or photocatalytic effects of the material on ecological receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Before performing the toxicity tests, it should be ensured that the AgNPs can be well dispersed in the culture medium. Therefore, it is recommended to characterize the test nanomaterial, including the degree of aggregation/agglomeration or change of particle size distribution (Kennedy et al 2017;Rasmussen et al 2018). This variation ideally may not be more than ± 20% (Petersen et al 2015).…”
Section: Agnps Physicochemical Characterizationmentioning
confidence: 99%